Research progress on resistance exercise therapy for improving cognitive function in patients with AD and muscle atrophy - Li, Wenyao; Fang, Wei; Zhang, Yier; Chen, Qiulu; Shentu, Wuyue; Lai, Qilun; Cheng, Lin; Yan, Sicheng; Kong, Qi; Qiao, Song (Frontiers in Aging Neuroscience, 2025)
Alzheimer's disease (AD) significantly reduces the quality of life of patients and exacerbates the burden on their families and society. Resistance exercise significantly enhances the overall cognitive function of the elderly and patients with AD while positively improving memory, executive function, and muscle strength, reducing fall risks, and alleviating psychological symptoms. As AD is a neurodegenerative disorder, some nerve factors are readily activated and released during exercise. Therefore, several prior studies have concentrated on exploring the molecular mechanisms of resistance exercise and their impact on brain function and neural plasticity. Recent investigations have identified an intrinsic relationship between individuals with AD and the pathological mechanisms of skeletal muscle atrophy, establishing a correlation between patients with AD cognitive level and skeletal muscle content. Resistance exercise primarily targets the skeletal muscle, which improves cognitive impairment in patients with AD by reducing vascular and neuroinflammatory factors and further enhances cognitive function in patients with AD by restoring the structural function of skeletal muscle. Furthermore, the effects of resistance training vary among distinct subgroups of cognitive impairment. Individuals exhibiting lower cognitive function demonstrate more pronounced adaptive responses in physical performance over time. Consequently, further investigation is warranted to determine whether tailored guidelines—such as variations in the frequency and duration of resistance exercise—should be established for patients with varying levels of dementia, in order to optimize the benefits for those experiencing cognitive impairment. This study aimed to review the relationship between AD and skeletal muscle atrophy, the impact of skeletal muscle atrophy on AD cognition, the mechanism by which resistance exercise improves cognition through skeletal muscle improvement, and the optimal resistance exercise mode to elucidate the additional advantages of resistance exercise in treating cognitive function in patients with AD and skeletal muscle atrophy.